The Evaluation of Physicomechanical and Tribological Properties of Corn Straw Fibre Reinforced Environment-Friendly Friction Composites - Zhen-yu Wang; Jie Wang; Yun-hai Ma (Advances in Materials Science and Engineering)
Corn stalk fibre reinforced nonasbestos environment-friendly friction composite materials have been fabricated, and their physical, mechanical, and tribological properties are characterized. The tribological properties of the friction composites were evaluated following GB5763-2008 norms on a constant-speed-type friction tester. The experimental outcome reveals that the content of corn stalk fibre has a noteworthy impact on the tribological, mechanical, and physical properties of the friction composites. Specifically, the friction composite with a content of 7% exhibited excellent friction and wear properties. The worn surface morphology of friction composites was further investigated using a scanning electron microscope. It was found that the corn stalk fibre content greatly affected the tribological properties of the friction composites.